Reforms in Poland – Opinions And Facts - Krajewski, Stefan; Osiecka, Katarzyna (Olsztyn Economic Journal, 2018)
In this paper we show that all attempts at major economic reforms introduced in Poland since the 1980s have incurred negative reactions on the part of large social groups (strikes, lack of support for the political forces which prepared and introduced reforms). We try to determine if such reactions are justified and whether there are serious arguments for them. We come to the conclusion that there were serious reasons for distrust and dislike of reforms. The main one involves the discrepancy between the declared goals and the assumed effects of reforms, and the actual effects felt by the public. Two issues will be presented: 1) to what extent are social feelings influenced by the demanding attitude of the public and its immaturity, which impede understanding of the need to reform the economy, 2) the inability of political elites to correctly formulate goals, identify the means of their implementation, and act effectively. The experience so far has made the political elites less and less interested in introducing serious reforms, which is manifested in the preference for a policy of providing basic utilities or relying on economic programs on the budgetary revenue generated by rising taxation.